ANALISIS DAN MAKNA TEOLOGI KETUHANAN YANG MAHA ESA DALAM KONTEKS PLURALISME AGAMA DI INDONESIA - Erman Sepniagus Saragih (Institut Agama Kristen Negeri Tarutung, 2018)
AbstrakIndonesia adalah bangsa yang majemuk. Keadaan ini berpeluang dan sensitif terhadap konflik sosial jika sikap toleran yang rendah, kepentingan politik dan fanatisme. Tujuan penulisan yaitu menemukan makna teologi “Ketuhanan” dalam konteks pluralisme agama. Metologi penelitian dilakukan dengan studi analisis isi. Kesimpulannya yaitu, pertama; kata ketuhanan tidak boleh difahami dari aspek agama tertentu saja dalam kemajemukan di Indonesia. Kedua; ketuhanan berarti sifat-sifat yang mengindahkan Tuhan sebagai tampilan antropomorfis oleh agama manapun. Ketiga; Ketuhanan merupakan hasil sejarah perumusan sila pertama Pancasila dengan kesadaran akan bhineka sebagai realita yang harus dirawat, dijunjung tinggi dan dihormati dalam berbagai aspek hidup melebihi agama. Kata Kunci : Ketuhanan Yang Maha Esa, Pluralisme Agama, Teologi AbstractA plural nation these circumstances are likely and sensitive to social conflict if low tolerance, political interests and fanaticism. The purpose of writing is to find the meaning of theology of as mentioned earlier in the context of religious pluralism. The methodology by content analysis, further interpret theologically. The concludes the theological meaning of God in the first principle of the Pancasila; is first, the meaning of divinity should not be understood from certain aspects of religion only in the context of pluralism in Indonesian. Second; divinity means the properties of God or attributes that need the God as an anthropomorphic appereance of and for any religions. Third; the sentences of “belief in the one and only God is the achierement of reconciliation of the historical resultsof the first principle of pancasila with the awareness of the difference as a reality that must be nurtured, upheld and respected in various aspects of life beyond certain religious values. Keywords: Ketuhanan Yang Maha Esa, Pluralism, Theology